Adventures in the solar system : Planetron and me - Williams, Geoffrey T.; Regan, Dennis F.; Svensson, Borje (Los Angeles : Price/Stern/Sloan, 1986)
A young boy takes a voyage through the solar system aboard a space ship and learns about the sun, planets, moons, and asteroids.
4.7
3-6
Keywords: Solar system -- Fiction; Outer space -- Exploration -- Fiction; Interplanetary voyages -- Fiction; Space -- Fiction